2018
DOI: 10.1186/s12882-018-1010-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting fistula failure in patients on chronic hemodialysis: a population–based case–control study

Abstract: BackgroundWith advancement of hemodialysis (HD) technique, late fistula failure (LFF) remains a problem significantly affecting life quality of patients. We attempt to identify factors affecting LFF in patients on chronic HD in Taiwan from the National Health Insurance Research Database.MethodsThis case–control study enrolled patients over 18 years old and who received regular HD for more than 3 months. LFF was defined as the first fistula failure episode beyond 3 months of chronic HD. We analyzed characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
1
9
0
1
Order By: Relevance
“…The present study contained 45% of patients with DM and 79% patients with hypertension, which was similar with the hemodialysis population reported in several previous studies 30 , 31 . In these studies, DM had been shown to be associated with a higher risk of AVF failure, which may be explained by increased thrombogenicity due to hyperglycemia 5 , 31 . On the contrary, another study showed that diabetes status was not associated with long-term AVF patency, which was in accordance with the findings in our study 32 .…”
Section: Discussionsupporting
confidence: 86%
“…The present study contained 45% of patients with DM and 79% patients with hypertension, which was similar with the hemodialysis population reported in several previous studies 30 , 31 . In these studies, DM had been shown to be associated with a higher risk of AVF failure, which may be explained by increased thrombogenicity due to hyperglycemia 5 , 31 . On the contrary, another study showed that diabetes status was not associated with long-term AVF patency, which was in accordance with the findings in our study 32 .…”
Section: Discussionsupporting
confidence: 86%
“…However, limited studies were designed to focus on the role of galectin-3 in hemodialytic patients. Vascular access dysfunction was critical point for hemodialytic patients, and diabetes affected the risk of shunt failure [34]. In addition to traditional medications for potential risk factors, current literature reported that drug-eluting balloon for recurrent AV shunt stenosis seemed to be a safe and beneficial therapy [35].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant clinical variables, namely past medical history (ischaemic heart disease, diabetes, previously failure vascular access attempt), medication history (antiplatelet and anticoagulant use at index) and HbA1c (immediately prior to index) were also recorded. 14 Data on subsequent interventions were also collected from electronic hospital records and recorded on a standardised form. Each patient was followed-up until access failure, renal transplant, death or 1st June 2018 (whichever sooner).…”
Section: Methodsmentioning
confidence: 99%